A perpendicular field electromagnet with a 250 mm access bore - Petrović, Alexander Paul (2021)
We present a laboratory electromagnet capable of generating magnetic fields up to ±0.48 T, specifically designed as a perpendicular flux source for thin film samples in an ambient environment. The magnet features a 250 mm diameter clear access bore above the sample plane, thus offering compatibility with a wide variety of experimental apparatus. Despite its generous size, the magnet thermally dissipates less than 1 kW at maximum field. A shaped ferromagnetic core is used to amplify and homogenize the field B, leading to an estimated uniformity of ±1.5 mT (≲0.3%) in B within a 28 mm2 zone at maximum field. The sample stage is thermally regulated and isolated from the magnet, enabling temperature control with ±5 mK precision even at elevated magnetic fields.